Committed to restoring tropical forests: an overview of Brazil's and Indonesia's restoration targets and policies. (1st September 2022) - Dockendorff, Constantino; Fuss, Sabine; Agra, Raquel; Guye, Valentin; Herrera, Diego; Kraxner, Florian
Abstract: The restoration of tropical forests has become a popular nature-based solution for climate change mitigation, protection of biodiversity, and improving the livelihoods of local populations. The Bonn Challenge and the UN Decade on Ecosystem Restoration underscore the international momentum of the restoration movement, with many countries committing to restore millions of hectares of deforested and degraded land in the next decade. Brazil and Indonesia are among the ones with the most ambitious restoration commitments globally. Since both their economies are highly dependent on the export of agricultural commodities, reconciling economic growth with environmental sustainability will be a major policy challenge. In this paper, we (a) identify the main restoration targets and the policies supporting their implementation in both countries, (b) provide a descriptive overview of these restoration-supportive policies, and (c) discuss the main challenges that Brazil and Indonesia face in the implementation of their restoration commitments. We find that Brazil has an explicit and dedicated strategy to achieve its restoration target, but that recent political developments have weakened environmental governance in the country, affecting the implementation of its restoration commitment. In the case of Indonesia, we find that the government has rather focused and progressed on the restoration of peatlands and mangroves, whereas its commitment to restore forestlands has yet to benefit from a dedicated plan that allows to coordinate policies and agencies' efforts towards the achievement of its restoration target.